City Branding for the Maritime Capital : The Role of the Baltic Sea in the Urban Space of Saint Petersburg - Andreeva, Mariia (My University, 2018)
The thesis “City Branding for the Maritime Capital” discusses the potential of developing an international brand for the city of St. Petersburg, Russia, based on the image of the Baltic Sea. Predisposition to this research is an understanding of inherent presence of the Baltic Sea in history, culture, and urban planning of this city, allowing the city to benefit from the image of the sea as a part of the Baltic Sea Region and thus regional community. However, existing brands emphasizing the sea connection are focused on the national factor (e.g. “St. Petersburg – the maritime capital of Russia”), lacking the links to regional narratives. To provide a basis for understanding the role of the Baltic Sea in the city, the thesis presents trends relevant for this topic from the time of the city foundation in the 18th century as well as from the 21st century to demonstrate the historical continuum recognizable in the urban space. Strategical development of the city can be traced over 300 years, allowing to mark a tendency of St. Petersburg urban space formulating two different narratives: internal city center connected with heritage preservation, and external space on the city outskirts, often on the Baltic Sea coast, that can be tied with the potential for future development and need for innovations and modernization. Current tendencies of promoting St. Petersburg are strongly connected with the internal factor, as the city more often brands its history rather than potential for modernization. Moving to practical application of branding strategies, the thesis focuses on city branding streamed through official city online media: websites of cities or city councils and administrations. The research presents how different cities around the Baltic Sea brand their location on the websites: highlighted historical events, introduced spheres of excellence, the wording chosen for branding. Based on the performed thematic analysis, the research suggests potential narratives and strategies that can be applied on the website of St. Petersburg to emphasize the innovative potential of the city benefitting from the image of the Baltic Sea.
Keywords: Saint Petersburg, Baltic Sea, Baltic Sea Region, city, branding, brand, urban space, online media